Analysis of the Ideals and Reality of the Leadership Style of the Ministry of School in the Application of the Pancasila Student Profile Strengthening Project - I Nyoman Yadi Anggara Putra; Kadek Hariana; Arif Firmansyah; Muchdar (Elementary Teacher Education Program, Majalengka University, 2024)
This research aims to describe the leadership style of the Principal of SDN Inpres 1 Lolu in implementing the Pancasila Student Profile Strengthening Project (P5). The type of research in this research is descriptive qualitative. The subjects in this research were the principal, class I (one) teacher, class II (two) teacher, class V (five) teacher, class VI (six) teacher, teacher in the field of Islamic religious studies, 1 class V (five) student and 2 students of class VI (six). The data collection techniques used in this research are observation, interviews and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. Meanwhile, the data validity checking technique uses source triangulation. The results of the research show that the leadership style applied by the school principal in the Implementation of the Project for Strengthening the Profile of Pancasila Students (P5) at SDN Inpres 1 Lolu tends to be democratic. This is reflected in the school principal's way of solving problems and making decisions. In this case, the Principal carries out discussions and deliberations with the staff and teachers. The principal's attitude is to always accept opinions, criticism and suggestions from subordinates well, be open-minded and sincere and participate actively in every activity at school. Apart from that, the school principal always develops and prioritizes a sense of unity and oneness such as togetherness and cohesiveness.